Evaluation of housing conditions in Europe using the TOPSIS method - Małgorzata Ćwiek; Paweł Ulman; Maria Sadko (Ekonomista, 2024)
This article assesses the housing conditions in European countries, and classifies those countries according to the state of their housing. Its main contribution is the use of a synthetic meter that uses the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) to classify housing conditions. The article utilises a wide set of variables that go beyond the scope of housing deprivation and take account of the impact of micro-district on housing quality. This paper fills a research gap in that it describes and compares housing conditions in European countries. Microdata from the European Union Statistics on Income and Living Conditions (EU-SILC) were used for this study. The conducted research shows that housing conditions in the vast majority of European countries are far from ideal. They are also considerably varied, both between and within countries, with respect to the assessment criteria.